An Unbiased Immunization Strategy Results in the Identification of Enolase as a Potential Marker for Nanobody-Based Detection of Trypanosoma evansi - Li, Zeng (Vaccines (Basel), 2020)
Trypanosoma evansi is a widely spread parasite that causes the debilitating disease “surra” in several types of ungulates. This severely challenges livestock rearing and heavily weighs on the socio-economic development in the affected areas, which include countries on five continents. Active case finding requires a sensitive and specific diagnostic test. In this paper, we describe the application of an unbiased immunization strategy to identify potential biomarkers for Nanobody (Nb)-based detection of T. evansi infections. Alpaca immunization with soluble lysates from different T. evansi strains followed by panning against T. evansi secretome resulted in the selection of a single Nb (Nb11). By combining Nb11-mediated immuno-capturing with mass spectrometry, the T. evansi target antigen was identified as the glycolytic enzyme enolase. Four additional anti-enolase binders were subsequently generated by immunizing another alpaca with the recombinant target enzyme. Together with Nb11, these binders were evaluated for their potential use in a heterologous sandwich detection format. Three Nb pairs were identified as candidates for the further development of an antigen-based assay for Nb-mediated diagnosis of T. evansi infection.